1986
DOI: 10.1111/j.1399-3054.1986.tb01226.x
|View full text |Cite
|
Sign up to set email alerts
|

14C Translocation pathways in honeylocust and green ash: Woody plants with complex leaf forms

Abstract: Long‐distance transport in plants requires precise knowledge of vascular pathways, and these pathways differ among species. This study examines the 14C translocation pathways in honeylocust (Gleditsia triacanthos L.) and green ash (Fraxinus pennsylvanica Marsh.), species with compound leaves, and compares them with those of cottonwood (Populus deltoides Bartr. ex Marsh.), a species with simple leaves. The stem vasculature of honeylocust conforms to a 2/5 helical phyllotaxy and that of green ash to a decussate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The llC experiments on individual plants demonstrate that even leaves at the same node may provide different translocation patterns and, depending on the leaf position, different speeds may be observed. After spot-feeding leaves of Populus deltoides with 14C02 (Vogelmann et al, 1982), or labelling individual leaflets of compound leaves of Fraxinus pennsylvanica (Larson and Dickson, 1986), it has been shown by microautoradiography that translocation occurred in specific bundles in leaves and stems and that changes may occur with ontogenetic development of the plant. Therefore, as far as possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The llC experiments on individual plants demonstrate that even leaves at the same node may provide different translocation patterns and, depending on the leaf position, different speeds may be observed. After spot-feeding leaves of Populus deltoides with 14C02 (Vogelmann et al, 1982), or labelling individual leaflets of compound leaves of Fraxinus pennsylvanica (Larson and Dickson, 1986), it has been shown by microautoradiography that translocation occurred in specific bundles in leaves and stems and that changes may occur with ontogenetic development of the plant. Therefore, as far as possible.…”
Section: Discussionmentioning
confidence: 99%
“…For the present studies, Fraxinus excelsior and Sorbus aucuparia were chosen to analyse possible differences in translocation of photoassimilates. Whilst the pinnate leaves and the shape of the young plants look quite similar, phyllotaxis of the vasculature is not the same (Larson and Dickson, 1986) and the sieve tubes of the two species differ markedly (Huber, 1939). Zimmermann and Ziegler (1975) reported that the main phloem translocates of Fraxinus species (Oleaceae) are stachyose and mannitol, whereas in Sorbus (Rosaceae), sorbitol and sucrose may be the translocated carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrate that sufficient resources do not move from non-stressed to stressed branches to compensate for the loss in photosynthetic area. Larson and Dickson 1973;Isebrands et al 1976;Larson 1977;Larson and Dickson 1986) are needed to confirm this. There are only four species in which damage to branches did not result in lowered fruit set or growth compared to control branches (Lee 1991;McCarthy & Quinn 1992;Obeso and Grubb 1993).…”
Section: Effects O F Damage Concentrated In a Single Branch Versus Comentioning
confidence: 98%
“…Second, the carbohydrates (e.g., soluble, nonstructural sugars) are perceived to be more stable in branch tips than the same components in leaves. These carbon-based compounds can vary diurnally within leaves and by leaf position on the branch (Dickson, 1986;and Larson and Dickson, 1986). Soluble sugars commonly are analyzed by two wet chemical methods (A and B), as described under "Laboratory Methods" below.…”
Section: Introductionmentioning
confidence: 99%